The effect of dietary astaxanthin and vitamin A supplementation on the reproductive performance of pond reared Penaeus monodon broodstock - Pangantihon, Ma. Paz Y. (Iloilo College of Fisheries, University of the Philippines in the Visayas, 1989)
The effect of astaxanthin and/or vitamin A on the reproductive performance of pond reared Penaeusmonodon was assessed in a 2x2 factorial experiment. The study was conducted in four 12m3, 1 m deep flow-through maturation tanks divided into two equal compartments using a nylon net. Doubly tagged prawn broodstock were utilized as individual replicates.Prawns were fed with broodstock diet with no supplements (Treatment A), with astaxanthin (Treatment B, vitamin A (Treatment C) and both astaxanthin and vitamin A (Treatment D) for 61 days. Results showed mean gonad index., which measures the degree of gonadal development, was significantly improved (P-0.05) by astaxanthin supplementation. The interaction between astaxanthin and vitamin A was not significant (P.0.05). Fecundity and egg hatching rate were not significantly affected (P.0.05) by the addition of supplemental astaxanthin and/or vitamin A in the diet. Mean fecundity and hatching rate, however were highest in prawn fed astaxanthin supplements (7.3 x 104 eggs/female and 5.7% hatching) and lowest in prawn nofed any supplements (3.2 x 104 eggs/female and 0% hatching). Further, mortality rate was highest in prawns fed both astaxanthin and vitamin A supplements (50%) and lowest in prawns nt fed with any supplements. High mortality was attributed to the high levels of synthetic astaxanthin and vitamin A inclusion. The results suggest direct involvement of astaxanthin in gonadal development and spawning, and thus a dietary astaxanthin requirement for reproduction of pond reared Penaeusmonodon. Moreover, early maturation of some prawns fed astaxanthin supplement suggests its effect on hastening ovarian maturation even without eyestalk ablation.
Thesis (M. S. Fisheries-Aquaculture) - University of the Philippines in the Visayas, October 1989.
Keywords: Prawn culture; Food additives; Penaeus monodon; Astaxanthin; Vitamin A; Spawning; Reproduction